Thrombolysis' benefits on early post-stroke language recovery in aphasia patients. (December 2019) - Menichelli, Alina; Furlanis, Giovanni; Sartori, Arianna; Ridolfi, Mariana; Naccarato, Marcello; Caruso, Paola; Pesavento, Valentina; Manganotti, Paolo
Highlights: Evaluation of aphasia is fundamental in the first phase of stroke. Data on evolution of early post-stroke aphasia following rTPA are still scarce. rTPA, baseline NIHSS and lacunar stroke were the predictors of aphasia recovery. rTPA improves the number of resolved aphasia patients in the early phase. Early post-stroke aphasia prognosis may be relevant for planning rehabilitation. Abstract: Introduction: Thrombolysis may affect ischemic stroke-related size, pattern and nature of infarcts, and has the potential to change aphasia presentation and recovery. Data on evolution of post-stroke aphasia following thrombolysis are still scarce. The aim of this study was to determine the course of language recovery through a well-validated language assessment battery after acute ischemic stroke and investigate whether traditional categorical classifications of aphasia can describe the clinical picture in post-thrombolysis phase. Materials and methods: Demographic, clinical, and language assessment data of 116 patients presenting sub-acute ischemic stroke aphasia (41 treated with r-tPA; 75 non-treated) were retrospectively analyzed. The participants were assessed by a clinical neuropsychologist with a variety of subtests taken from a well-validated Italian language battery (Neuro-Psychological Aphasia Evaluation). Results: The percentage of resolved aphasia was significantly higher in treated patients compared to non-treated patients ( p  = 0.005) and global aphasia was more common in the non-treated group (non-treated 30.7% vs treated 17.1%). Aphasia subtypes and stroke etiologies showed no significant association, except for small vessel etiology and resolved aphasia ( p  = 0.041). Reperfusion treatment, baseline NIHSS, and lacunar stroke were the predictors of aphasia recovery. Conclusion: The percentage of resolved aphasia was significantly higher in the treated patients compared to the non-treated, with the latter showing a higher percentage of global aphasia. Identifying classic aphasia subtypes after thrombolysis is still possible since reperfused areas do not necessary change the classification or lead to completely different aphasic syndromes. Reperfusion treatment, baseline NIHSS, and lacunar stroke were the main predictors of aphasia recovery.